Corneal biomechanical properties following corneal cross-linking: Does age have an effect?. (January 2022) - Alenezi, Bandar; Kazaili, Ahmed; Akhtar, Riaz; Radhakrishnan, Hema
Abstract: Purpose: To explore the effect of age on corneal biomechanical properties following corneal cross-linking (CXL). Methods: A total of 12 pairs of human eye-banked corneas (24 corneas, from 14 females and 10 males) were used in the study. The mean donor age was 48.5 years (ranging from 26 to 71 years). Corneas were divided into three age groups: A (26–41 years), B (42–57 years) and C (58–71 years), with four pairs in each group. For each pair, the right corneas were cross-linked using accelerated CXL with UVA (10 mW/cm 2 ) and riboflavin, while the left corneas served as controls and were not exposed to either UVA irradiation or riboflavin. The corneal elastic modulus of the anterior, mid and posterior corneal stroma was measured using nanoindentation. Results: The difference in the corneal elastic modulus following CXL was significant in the anterior ( p = 0.00002) and mid stroma ( p = 0.001); however, the difference was not significant in the posterior stroma ( p = 0.27) when compared to control corneas. The corneal elastic modulus of the anterior stroma increased by 178.44% in Group A, 119.7% in Group B and 50.73% in Group C compared to control corneas. For the mid stroma, the elastic modulus increased by 47.35% in Group A, 25% in Group B and 24.56% in Group C. No differences were observed in the posterior stroma between age groups. Conclusions: Corneal elasticity showed a greater response to CXL in the younger group compared to older groups. CXL treatment showed effectiveness in enhancing stromal strength, and the effect was concentrated in the anterior and mid stroma with minimal impact on the posterior stroma in all age groups. Highlights: Cross-linking (CXL) is more effective in younger corneas. CXL effect is more concentrated on the top half of the cornea. Nanoindentation is ideal for measuring corneal biomechanics.